Diagnostic Features and Selection of Hypolipidemic Therapy in Patients with Coronary Artery Disease with “Possible” Familial Hypercholesterolemia - Mitchenko, Olena I.; Timokhova, Kateryna O.; Chulaievska, Nataliia M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To optimize the diagnostic algorithm for patients with true “possible” familial hypercholesterolemia (FH) and differential diagnosis with hypercholesterolemia on the background of comorbid endocrinopathies for selection of optimal hypolipidemic therapy. Materials and methods. We examined 130 patients with hypercholesterolemia and comorbid pathology (type 2 diabetes mellitus, hypothyroidism, obesity grade II-III). In each group, subgroups with low-density lipoproteins (LDL) ≥5 mmol/l were selected and followed up on the background of maximum tolerated doses of statins in combination with therapy aimed to compensate comorbid pathology. The control group consisted of 20 patients with verified FH. Results and discussion. Combined dyslipidemia was detected in groups 1 and 3, pure hypercholesterolemia in group 2. Direct correlations between lipid profile and comorbid pathology characteristics were revealed. Patients of the subgroups with “possible” FH had higher atherogenicity of the lipid profile associated with comorbid pathology destabilization and high percentage of atherosclerosis of carotid and coronary arteries. According to the results of the follow-up, it was established that statin therapy and comorbid pathology compensation led to the achievement of target levels of LDL (group 3) or a reduction of LDL by 50% (group 1, 2). In patients of the control group, statin therapy with maximally tolerated doses did not show such results. Conclusions. The cohort of patients defined as having “possible” FH is heterogeneous and may include patients with secondary dyslipidemia on the background of comorbid pathology destabilization, timely verification and treatment of which contributes to achieving the goals of lipid-lowering therapy. Taking into account that only obese patients reached the target level of LDL <1.8 mmol/l, combined lipid-lowering therapy is recommended for patients with hypothyroidism and diabetes. Refractoriness to statin therapy in patients with verified “possible” FH emphasizes the need for combined lipid-lowering therapy (ezetimibe, PCSK9 inhibitors).